2002
DOI: 10.1034/j.1600-6143.2002.20502.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold Storage Preservation and Warm Ischaemic Injury to Isolated Arterial Segments: Endothelial Cell Injury

Abstract: Injury to endothelial cells is thought to be important to the development of the vascular lesion of chronic rejection. It was the aim of this study to develop a semiquantitative method to assess endothelial injury in arterial grafts and to document the injury produced by cold storage preservation and additional warm ischaemia. Twelve-and 24-h cold preservation of rat aortic segments, together with an additional 1 h of warm ischaemia, were assessed. Electron micrographs of representative endothelial cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Cold storage of vascular endothelial cells has been shown to induce increased adhesion of platelets, 36 and storage of vessels has been shown to disrupt the endothelial monolayer. 37,38 Both might lead to thrombosis and graft occlusion, which could result in the loss of the organ/tissue supplied by the grafted vessel. 39,40 In solution 8 with 0.1 mmol/L deferoxamine ϩ 20 mol/L LK 614, the platelet adherence was significantly reduced compared with HTK solution, indicating lower thrombogenicity.…”
Section: Role Of Chloridementioning
confidence: 99%
“…Cold storage of vascular endothelial cells has been shown to induce increased adhesion of platelets, 36 and storage of vessels has been shown to disrupt the endothelial monolayer. 37,38 Both might lead to thrombosis and graft occlusion, which could result in the loss of the organ/tissue supplied by the grafted vessel. 39,40 In solution 8 with 0.1 mmol/L deferoxamine ϩ 20 mol/L LK 614, the platelet adherence was significantly reduced compared with HTK solution, indicating lower thrombogenicity.…”
Section: Role Of Chloridementioning
confidence: 99%
“…A recent study 15 has addressed endothelial structural changes of rat abdominal aorta after 24 hours of storage in University of Wisconsin (UW), Collins, and Euro-Collins solutions. Endothelial cell structure was maintained after 24 hours only in UW-solution.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 A 24-48 hour period of successful endothelium and microvessel preservation during cold storage has been reported. [15][16][17] It seems highly desirable to extend this period and improve the availability of donor tissues. A recent experimental study reported substantial progress with respect to long-term storage of pig aortic segments over 3 weeks.…”
mentioning
confidence: 99%
“…At the cellular level, the mitochondria and the endoplasmic reticulum are the principal organelles affected [36], with the result that cells are constrained in adapting their biochemical programs. Indeed, ischemia triggers a switch in energy production by activating glycolysis in anaerobic conditions, leading to a sudden fall in ATP concentration due to a lower yield of ATP production compared to oxidative phosphorylation.…”
Section: Strategies To Limit Renal Ischemia-reperfusion Injuries and mentioning
confidence: 99%